The Relationship Between Knowledge and Parental Behavior in Children's Sex Education - Ami Linda Kustati; Kartika Adyani; Friska Realita (EMBRIO: Jurnal Kebidanan, 2024)
Parents are the leading figures in providing sex education, sex education is important considering the large number of cases of sexual violence against children. The behavior of providing sex education to children must be patient and repeated over and over again so that the child understands. Parents can also teach children to protect themselves and dare to say no when someone tries to make their child undress. Objective: To determine the relationship between knowledge and parental behavior in providing child sex education in Kesambi Hamlet, South Prupuk Village, Margasari District, Tegal Regency. Method: This type of research is quantitative with a cross-sectional approach. Population 62 Respondents. The sampling technique is simple random sampling, done by randomizing each neighborhood. Data was collected using a questionnaire, and analysis was carried out using the Chi-Square test. Results: This study showed that 43 (69.4 percent) had good knowledge, and 44 (71.0 percent) respondents had positive behavior. Moreover, based on the Chi-Suqre test, p (0.00) was found. There is a relationship between knowledge and parental behavior in providing child sex education in Kesambi Hamlet, South Prupuk Village, Margasari District, Tegal Regency.